Technical and tactical preparedness of the team «Helios» of Kharkov in the 25th football championship of Ukraine in the first league (the first round) in 2015 - Журід, Сергій Миколайович; Слеман, Ребаз (Slobozhanskyi Herald of Science and Sport, 2016)
Zhurid S., Rebaz Sleman Purpose: to define model characteristics of technical and tactical preparedness of the team which participated in the championship of Ukraine of the first league for the purpose of further improvement and correction of the educational and training process. Material & Methods: researches were carried out by means of method expert estimates. 5 specialists of football were involved as experts. Results: average values of the registered sizes for 10 games were analyzed. Various technical and tactical actions and their differences for the first and second times, and also separate indicators of a game of players and the team «Helios» of Kharkov are analyzed. Conclusions: quantitative and qualitative indicators (flaw coefficient) were received as on team technical and tactical actions, and separately on each technical-tactical technique for every period of a game.